A concise review of lenalidomide therapy for follicular lymphoma. (4th March 2017) - Bari, Alessia; Marcheselli, Raffaella; Barbolini, Monica; Ferri, Paola; Sacchi, Stefano; Pozzi, Samantha
ABSTRACT: Introduction : Lenalidomide, first introduced for the treatment of multiple myeloma in 2008, has been used in the treatment of various subtypes of non-Hodgkin lymphoma (NHL). Considering its mechanism of action, it has been associated with rituximab, showing strong activity in follicular lymphomas (FL). As the chemo-free treatments are a topic of great relevance we decided to prepare a concise review mainly directed to clinicians involved in the management of NHL patients. Areas covered : This article reviews the clinical trials published since 2008 utilizing lenalidomide alone or in combination for treating relapsed/refractory or treatment naïve patients with FL. Expert opinion : With current rituximab plus chemotherapy treatments, almost all patients will relapse from the disease over time. The introduction of lenalidomide in the management of FL showed good efficacy in particular in combination with rituximab (R2). The high rates of durable responses obtained with the R2 combination were similar to those previously observed with standard chemotherapy plus rituximab. If the results of the ongoing multicenter pivotal phase 3 trial (NCT01476787) are favorable for R2 combination, we may move towards a chemotherapy-free approach in the management of FL, which would finally turn a dream into reality.